Examining the adoption of big data and analytics curriculum. Issue 3 (5th June 2017) - McLeod, Alexander J.; Bliemel, Michael; Jones, Nancy
Abstract : Purpose: The purpose of this paper is to explore the demand for big data and analytics curriculum, provide an overview of the curriculum available from the SAP University Alliances program, examine the evolving usage of such curriculum, and suggest an academic research agenda for this topic. Design/methodology/approach: In this work, the authors reviewed recent academic utilization of big data and analytics curriculum in a large faculty-driven university program by examining school hosting request logs over a four-year period. The authors analyze curricula usage to determine how changes in big data and analytics are being introduced to academia. Findings: Results indicate that there is a substantial shift toward curriculum focusing on big data and analytics. Research limitations/implications: Because this research only considered data from one proprietary software vendor, the scope of this project is limited and may not generalize to other university software support programs. Practical implications: Faculty interested in creating or furthering their business process programs to include big data and analytics will find practical information, materials, suggestions, as well as a research and curriculum development agenda. Originality/value: Faculty interested in creating or furthering their programs to include big data and analytics will find practical information, materials, suggestions, and a research and curricula agenda.